ПОРІВНЯЛЬНИЙ АНАЛІЗ ХАРАКТЕРИСТИК ЕЛЕКТРОДВИГУНІВ З ПОСТІЙНИМИ МАГНІТАМИ ДЛЯ ЕЛЕКТРОМОБІЛІВ - Гребеніков, В.В.; Павлов, В.Б.; Гамалія, Р.В.; Попков, В.С.; Бондаренко, С.Г. (Інститут електродинаміки НАН України, Київ, 2024)
The results of numerical investigation of electric motors with permanent magnets of cylindrical type are presented. It is shown that replacement of a squirrel-cage rotor in a standard induction motor by a rotor with permanent magnets allows to obtain a significant increase in the specific power of the electric machine. Numerical investigations and analysis of characteristics of the electric motor with tangentially magnetized neodymium magnets for five configurations of the rotor magnetic system are carried out. It is shown that to ensure maximum specific characteristics in electric motors for electric vehicles it is necessary to take into account the driving cycle and to carry out liquid cooling of the electric motor. Thermal calculations taking into account the driving cycle of NEDC are also performed and it is established that the use of liquid cooling allows to provide cooling of neodymium magnets and windings to a temperature lower than critical at increased current in the windings. Characteristics of the investigated electric motors are calculated in Simcenter MagNet and Simcenter MotorSolve software packages. References 4, figures 5, tables 1.